DAY OF THE WEEK EFFECT TERHADAP RETURN DAN VOLUME PERDAGANGAN SAHAM LQ45 DAN NON LQ45 - Yanuar Bachtiar (Jurnal Keuangan dan Perbankan, 2009)
This research aimed to know: fi rst, day of the week effect that infl uence the return of LQ45and non LQ45 stocks. Second, to know day of the week effect that infl uenced the volume of commerceof LQ45 and non LQ45 stocks. The taken samples were a property stock and real estate stocksincluding 2 stocks that was part of LQ45 and 2 other stocks in non LQ45 at Jakarta Stock Exchange(JSX) in January up to December 2006 (242 trade days) by fulfi lling samples which were already valid.Analysis model used in this research was linear regression model. The result of this research showedthat the lowest return found on Monday trade days and the lighest return was on Friday trade day.However, day of the week effect only proved signifi cant at stock non LQ45 group. The trial on tradevolume did not fi nd any signifi cant result.